Isolated Epileptiform EEG Discharges and Autism - J Gordon Millichap (Pediatric Neurology Briefs, 2009)
The relationship between EEG abnormalities and neuropsychiatric disorders, and their possible clinical significance are reviewed by an investigator at Wayne State University, Detroit, MI, with special attention to the EEG and autism.